A review of the subgenera Carinichelonus, Microchelonus, Parachelonus and Stylochelonus of the genus Chelonus Panzer (Braconidae: Cheloninae) with descriptions of twenty-one new species from China - Zhou, Jin-Jin; Achterberg, Cornelis Van; Tang, Pu; Chen, Xue-Xin (Zootaxa, 2024)
Three subgenera Microchelonus Szépligeti, 1908 s. str., Parachelonus Tobias, 1995 and Stylochelonus Hellén, 1958 are newly recorded from China, 21 new species, viz., C. (M.) adiazetos sp. nov., C. (M.) aequus sp. nov., C. (M.) brachykeraiatus sp. nov., C. (M.) bullatus sp. nov., C. (M.) clivus sp. nov., C. (M.) crassitibialis sp. nov., C. (M.) cyclotus sp. nov., C. (M.) erugatus sp. nov., C. (M.) illatus sp. nov., C. (M.) leious sp. nov., C. (M.) linzhiensis sp. nov., C. (M.) maculovittatus sp. nov., C. (M.) melanochromus sp. nov., C. (M.) platyetrus sp. nov., C. (M.) recavus sp. nov., C. (M.) ruficorpus sp. nov., C. (M.) scirpophagae sp. nov., C. (M.) staurorhytis sp. nov., C. (P.) hirsutus sp. nov., C. (S.) acaretrus sp. nov., and C. (S.) punctulosus sp. nov. are described and illustrated. Also, eleven species are reported as new to China: C. (M.) alticinctus (Tobias, 1989), C. (M.) alveatus (Tobias, 1989), C. (M.) calcaratus (Tobias, 1989), C. (M.) flagellaris (Tobias, 1989), C. (M.) insidiatrix (Tobias, 1989), C. (M.) milkoi (Tobias, 2003), C. (M.) moskovitus (Tobias, 1997), C. (M.) semilunaris (Tobias, 2000), C. (M.) temporalis (Tobias, 1986), C. (M.) varus (Tobias, 2000) and C. (M.) zaitzevi (Tobias, 1972). Four new combinations are proposed: C. (P.) compressor (Chen & Ji, 2003) comb. nov., C. (P.) macrocorpus (Ji & Chen, 2003) comb. nov., C. (P.) polycolor (Chen & Ji, 2003) comb. nov. and C. (Baculonus) rubriventris (Tobias, 1988) comb. nov. The following new names are proposed: C. (M.) jiae nom. nov. for C. (M.) bimaculatus (Chen & Ji, 2003) and C. (M.) substernatus nom. nov. for C. (M.) tobiasi (Yuldashev, 2011). Microchelonus (Carinichelonus) cavifrons Tobias, 2000 is synonymized with C. (Ca.) tabonus Sonan, 1932. A key to the Chinese species of the subgenus Microchelonus is provided together with keys to the currently known species of the subgenera Carinichelonus, Stylochelonus and Parachelonus.